Awareness of HIV functional cure and willingness in participating in related clinical trials: comparison between antiretroviral naïve and experienced men who have sex with men living with HIV - Tsz Ho Kwan; Chin Pok Chan; Ngai Sze Wong; Shui Shan Lee (BMC Infectious Diseases, 2022)
Abstract Background Human immunodeficiency virus (HIV) functional cure is a novel biomedical strategy characterized by sustained viral suppression without the need for life-long medications. The attitude of people living with HIV (PLHIV) towards functional cure and clinical trials are understudied. We aimed to examine the awareness and levels of anticipation for HIV functional cure among men who have sex with men (MSM) living with HIV, and their willingness to join trials as differentiated by their antiretroviral treatment status. Methods MSM living with HIV with and those without treatment history were recruited from Hong Kong’s HIV specialist clinics. Self-administered questionnaires covering behavioral profile, perceived impact of HIV cure, attitude towards HIV functional cure and related clinical trials were collected. Clinical data were separately transcribed. Determinants of perceptions and attitudes were identified by logistic regression models. Results Of 356 MSM living with HIV recruited, less than half (42%) were aware of HIV functional cure, but they had a high level of anticipation for it. Treatment-experienced participants were more likely to be aware of HIV functional cure. Awareness was associated with continued engagement in sexual activities after HIV diagnosis and sexually transmitted infection (STI) diagnosis. Higher anticipation was observed among older MSM living with HIV but it was negatively associated with one’s awareness. Over 90% were willing to join functional cure trials, especially those who had previously been diagnosed with STI and had engaged in chemsex in the past year. Advice from healthcare professional was an important factor considered by those willing to join clinical trials. Younger, better educated MSM, and those with lower CD4 counts were more concerned about potential risk of AIDS and potential complications upon trial participation. Conclusions MSM living with HIV, especially those sexually active, showed positive attitude towards functional cure and willingness to join related clinical trials despite low awareness. To enhance preparedness for HIV functional cure trials, community education, updated information and appropriate medical advice would be needed. Safety is a major concern for potential enrollees in HIV functional cure trials.